Diversity and spatial distribution of black flies (Diptera: Simuliidae) in the Ijuí river drainage basin, Rio Grande do Sul, Brazil - Menzel, Tieli Cláudia; Hentges, Sirlei Maria; Reynalte Tataje, David Augusto; Strieder, Milton Norberto (EntomoBrasilis, 2019)
Abstract. In southern Brazil there are several problems regarding the hematophageal activity of black flies, and the information on the distribution of species are still insufficient. In this study, our main goals were to recognize Simuliidae species and to analyze abiotic factors regarding the distribution of immature stages (larva and pupa) in streams from the Ijuí River basin, Northwest of Rio Grande do Sul, Brazil. We sampled simulids specimens in 27 study sites, covering three regions (high, intermediate and low altitude). Concomitantly, we recorded abiotic factors in the studied sites, such as: temperature, electrical conductivity, dissolved oxygen, atmospheric pressure, pH, altitude and stream width. For data analysis, we performed Kruskal-Wallis, ANOVA, Principal Component Analysis (PCA), Analysis of Indicator Species and Canonical Correspondence (CCA). A total of 10 species of black Flies was recorded. Simulium pertinax Kollar, Simulium incrustatum Lutz and Simulium orbitale Lutz were the most frequent. There was no significant difference in richness and density of the species between the different regions studied, except for Simulium jujuyense Paterson & Shannon. The sampled environments were segregated according to the location within the basin, and only S. jujuyense was considered an indicator species of the upper region. These results can be explained by the homogeneous conditions of the Ijuí River basin, which have suffered anthropogenic pressure mainly due to agricultural activities, resulting in losses in local aquatic biodiversity. Also, it may indicate that the control must be conducted considering the basin as a whole, and not only as isolated stretches of the streams. Diversidade e distribuição espacial de borrachudos (Diptera: Simuliidae) na bacia hidrográfica do rio Ijuí, Rio Grande do Sul, Brasil Resumo. No sul do Brasil existem problemas com atividade hematofágica de borrachudos e as informações referentes à distribuição das espécies ainda são insuficientes. O presente estudo visa reconhecer as espécies de Simuliidae e analisar fatores abióticos quanto a distribuição dos estágios imaturos (larva e pupa) em riachos da Bacia do Rio Ijuí, no Noroeste do Rio Grande do Sul, Brasil. Foram coletados simulídeos em 27 pontos de estudo, cobrindo três regiões da bacia (alta, intermediária e baixa altitude). Concomitantemente, foi feito o registro de fatores abióticos nos trechos estudados, tais como: temperatura, condutividade elétrica, oxigênio dissolvido, pressão atmosférica, pH, altitude e largura do riacho. Foram realizadas análises de Kruskal-Wallis ou ANOVA, Análise de Componentes Principais (PCA), Análise de Espécie Indicadora e de Correspondência Canônica (CCA). Foi registrado um total de 10 espécies de Simuliidae. Simulium pertinax Kollar, Simulium incrustatum Lutz e Simulium orbitale Lutz foram as mais frequentes. Não ocorreu diferença na riqueza e na densidade das espécies entre as diferentes regiões estudadas, exceto para Simulium jujuyense Paterson & Shannon. Os ambientes nos pontos de amostragem foram segregados de acordo com a sua localização na bacia, e apenas S. jujuyense foi considerada uma espécie indicadora da região alta. Tais resultados podem ser explicados pelas condições homogêneas da Bacia do Rio Ijuí, que vêm sofrendo pressão antropogênica principalmente devido às atividades agrícolas, resultando em perdas na biodiversidade aquática local. Também, indicam que o controle deve ser realizado considerando a bacia como um todo e não apenas em trechos isolados dos riachos.